LINGUISTIC ANALYSIS OF UZBEKPOTTERY TERMS (Scientific journal of the Fergana State University, 2023)
In this article, using examples, the role of Uzbek ceramic terms in the language, sources of enrichment, their thematic classification is presented, the etymological layer and features of the vocabulary of ceramics are classified, as well as their explanation.